(untitled) (Italian Journal of Public Health, 2005)
The aim of the present survey was to assess the perceived risk of foodborne infections in young adults with a high education level. The authors investigated their knowledge of foodborne infections, the preparation and storage of food that favour these infections and the rules of food safety and hygiene for consumer protection, as well as their behaviour regarding personal hygiene and their eating habits outside the home. The results showed that they had a good level of knowledge across all of the fields investigated, but outside the home they tended to favour food products that have a high risk of foodborne infection. This confirms that lifestyle and eating habits are strongly influenced by socio-economic factors, fashion, the media and by the market demands of the food industry.